2015
DOI: 10.2355/isijinternational.55.1252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Dissolution Reaction on Wetting Behavior between Liquid Iron and Carbonaceous Material

Abstract: A low carbon operation is an unfavorable situation for liquid permeability around cohesive zone, because liquid volume will increase against solid coke in there. In order to keep a healthy operation with this technique, information of wetting behavior between liquid iron and coke should be correctly understood. However, there is not enough information about wetting behavior between them, because of many difficulties about wettability measurement from an active reaction between iron and carbonaceous materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…[10][11][12][13] In our previous studies, the apparent contact angles values at 1 673 K decreased during the initial contact period from 120, 123, 125° to 87, 90, 105° of Fe-3.70, 4.26, 4.90 mass% C samples, respectively. 10,11) And, the apparent contact angles also increased with increasing of the initial carbon concentrations of the Fe-C sample.…”
Section: Apparent Contact Angles Between Fe-c Samplementioning
confidence: 71%
See 2 more Smart Citations
“…[10][11][12][13] In our previous studies, the apparent contact angles values at 1 673 K decreased during the initial contact period from 120, 123, 125° to 87, 90, 105° of Fe-3.70, 4.26, 4.90 mass% C samples, respectively. 10,11) And, the apparent contact angles also increased with increasing of the initial carbon concentrations of the Fe-C sample.…”
Section: Apparent Contact Angles Between Fe-c Samplementioning
confidence: 71%
“…11) In the previous study, intrusion of iron in the substrates after contact period of 1 800 s was observed. In other words, carbon atoms dissolved into the Fe-C sample at high temperature due to the carbon dissolution reaction, which led to the appearance of the region for occupancy of the liquid Fe-C in the substrate.…”
Section: Effect Of Carbon Dissolution On the Apparent Con-mentioning
confidence: 88%
See 1 more Smart Citation
“…The wettability between carbon and slag in a blast furnace was thoroughly described by Mukai et al 9) and Barrett et al 10) Measurements of the contact angle between the coke and liquid have been conducted in recent years considering the influence of ash. 11,12) The contact angle between pig iron and coke is 60-130°. 13) In addition, this angle changes with a change in the carbon or sulfur concentration in the iron.…”
Section: )mentioning
confidence: 99%
“…[1][2][3][4][5] In turn, this causes the blast furnace to perform more favourably and efficiently, and consequently, reduces fuel consumption of the blast furnace and suppresses CO 2 emissions. Therefore, the behaviour of the liquid phase dripping through this area is significant to the blast furnace operation.…”
Section: Introductionmentioning
confidence: 99%